2021
DOI: 10.1002/prot.26264
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical studies of an iterative ribosomal peptide macrocyclase

Abstract: Microviridins, tricyclic peptide natural products originally isolated from cyanobacteria, function as inhibitors of diverse serine-type proteases. Here we report the structure and biochemical characterization of AMdnB, a unique iterative macrocyclase involved in a microviridin biosynthetic pathway from Anabaena sp. PCC 7120. The ATPdependent cyclase, along with the homologous AMdnC, introduce up to nine macrocyclizations on three distinct core regions of a precursor peptide, AMdnA. The results presented here p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…When the monomers in an experimental structure adopt different conformations, the predicted structures are more similar to one monomer than the other, resulting in a set of values that show high similarity and a set of values that show similarity like that of the comparison between the experimental monomers. The larger spread in the similarity for RiPP biosynthetic enzymes could be due to a number of experimental structures including bound precursor peptide, the binding of which is known to cause structural rearrangements [ 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the monomers in an experimental structure adopt different conformations, the predicted structures are more similar to one monomer than the other, resulting in a set of values that show high similarity and a set of values that show similarity like that of the comparison between the experimental monomers. The larger spread in the similarity for RiPP biosynthetic enzymes could be due to a number of experimental structures including bound precursor peptide, the binding of which is known to cause structural rearrangements [ 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…A set of seven different enzymes belonging to the ATP-grasp ligase family were modeled using the ColabFold v1.3 implementation of the AlphaFold 2.1 with the mmseq2 software package (installed locally) [ 15 , 16 , 25 , 26 ] both as monomers and dimers. The different enzymes utilized for this portion of the study included the RiPP biosynthetic enzymes MdnC (5IG9) [ 27 ], MdnB (5IG8) [ 27 ], aMdnB (7M4S) [ 28 ], CdnC (7MGV) [ 29 ], and PsnB (7DRM) [ 30 ], as well as ATP-grasp ligases that are not involved in RiPP biosynthesis, ArgX (3VPB) [ 31 ] and LysX (3VPD) [ 31 ]. The two enzymes that are not involved in RiPP biosynthesis were chosen due to their structural similarity to the RiPP biosynthetic enzymes, as well as their thorough structural and mechanistic characterization.…”
Section: Methodsmentioning
confidence: 99%
“…All of the putative precursor peptides contain a highly conserved PFFAxFL α-helix motif at the N-terminus of leader peptides in which x could be a positive or noncharged amino acid S/T/Q/N/R/A (listed in the order of abundance), while it is generally R in cyanobacteria (Figure S1B). This motif was known as a recognition motif for ATP-grasp ligases. , Studies showed that the amide bond could not be formed when R was mutated to N . The mutations of each single amino acid within this motif led to the production of bicyclic microviridins instead of tricyclic microviridins .…”
Section: Resultsmentioning
confidence: 99%
“…This motif was known as a recognition motif for ATP-grasp ligases. 4,41 Studies showed that the amide bond could not be formed when R was mutated to N. 36 The mutations of each single amino acid within this motif led to the production of bicyclic microviridins instead of tricyclic microviridins. 36 The variable x residue might suggest different substrate recognition by the ATP-grasp ligases from different bacteria.…”
Section: Analysis Of Microviridin Bgcs From Bacteroidetesmentioning
confidence: 99%